The new world of work : people leadership in the digital age - Biswas, Bashker, 1944-; Garrison, William; Ramirez, Robert L. (New York, NY : Routledge, 2023)
"Arguing that a functional approach to human resource management is fast becoming obsolete, this book explores the many areas of accelerated change in the workplace and how business leaders must evolve their thinking to meet the needs of their workers and managers alike. With a clear focus on the accelerations caused by Covid-19 and how technological platforms have enabled working practices and business continuity, the book effectively lays the groundwork for a changed but well-functioning people management system. The authors present the new model of Strategic Human Asset Lifecycle Management that incorporates the drastic changes in how jobs are designed, how human talent is acquired, how work is performed, how work is rewarded and conditions set, and crucially, how labor laws must change-all to meet the fast-moving requirements of a digitized world. Enriched with cases that illustrate both well- and badly-adapted organizations, as well as helpful summaries and thought-provoking challenges, this book is an essential resource for all those who aspire to great people leadership in their organizations, including HR professionals, instructors and upper-level students"--
Keywords: Personnel management -- Technological innovations; Management information systems; Leadership; Organizational change; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Management